2019
DOI: 10.1002/mbo3.909
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale distribution of bacterial communities in the Qaidam Basin of the Qinghai–Tibet Plateau

Abstract: Many studies have investigated patterns of soil microbial communities over large spatial scales. However, these studies mainly focused on a few sites. Here, we studied the near‐surface (0–30 cm) soil microbial communities of 35 soil samples collected from most of the areas of the Qaidam Basin, which is the largest basin on the Qinghai–Tibet Plateau. A total of 32 phyla and 838 genera were detected from all the samples, in which Actinobacteria, Proteobacteria, Bacteroidetes, and Acidobacteria were the most domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 41 publications
9
20
0
Order By: Relevance
“…The surface soil samples had higher α-diversity indices (Chao, Shannon, and Simpson) ( Supplementary Table 1 and Figure 2), the highest modularity index in the co-occurrence network, and the largest number of biomarker taxa. The level of diversity in this study indicates a more complex ecosystem in the Qaidam Basin than previously reported by Xing et al (2019). The present data showed that the view based on soil analyses indicate that bacterial phyla such as Firmicutes, Proteobacteria, FIGURE 6 | The potential biomarker was defined by LEfSe.…”
Section: Bacterial Diversity In the Qaidam Basinsupporting
confidence: 52%
See 4 more Smart Citations
“…The surface soil samples had higher α-diversity indices (Chao, Shannon, and Simpson) ( Supplementary Table 1 and Figure 2), the highest modularity index in the co-occurrence network, and the largest number of biomarker taxa. The level of diversity in this study indicates a more complex ecosystem in the Qaidam Basin than previously reported by Xing et al (2019). The present data showed that the view based on soil analyses indicate that bacterial phyla such as Firmicutes, Proteobacteria, FIGURE 6 | The potential biomarker was defined by LEfSe.…”
Section: Bacterial Diversity In the Qaidam Basinsupporting
confidence: 52%
“…change effects are most pronounced in desert regions and as there could be increases in localized cooling in the Qaidam Basin (Xing et al, 2019), it is timely to explore this endangered environment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations